Metzia parva, a new cyprinid species (Teleostei: Cypriniformes) from south China - Luo, Wen; Sullivan, John P.; Zhao, Hai-Tao; Peng, Zuo-Gang (Zootaxa, 2015)
A new species of a small cyprinid fish, Metzia parva sp. nov., is described here based on specimens collected from a tributary of Hongshui-He River in the Pearl River basin at Anyang Town, Du’an County, Guangxi Province, south China. It differs from congeners in having a smaller body with a standard length of 48.3–57.7 mm (vs. 58.3–151.4 mm in other species); a complete lateral line (although some specimens show interruptions on the ventral margin above the anal-fin); 12–14 branched anal-fin rays (vs. 10–11 or 15–20); 10 branched pectoral-fin rays (vs. 11–16); 6 branched pelvic-fin rays (vs. 7–9); a longer caudal peduncle (17.8–21.7% vs. 14.8–17.4% SL); a shorter preanal length (60.9–66.0% vs. 69.0–73.0% SL) and an obviously larger interorbital width (28.4–33.0% vs. 20.2–24.7% of head length). While Metzia parva shares a lateral black stripe from the gill opening to the caudal-fin base with M. formosae, the new species can be distinguished from M. formosae by a deeper head (16.4–19.2% vs. 13.3–15.7% SL) and a longer anal fin (15.4–18.9% vs. 10.0–13.6% SL) in addition to the diagnostic characters above. Kimura’s 2-parameter genetic distance between the two species is 6.6% for the barcoding region of the mitochondrial COI gene and 7.3% across the complete mitochondrial genome.